Preparation method and application of three-dimensional hierarchical ordered mesoporous zeolite confinement NiCo alloy catalyst
By preparing a limited-domain NiCo alloy catalyst in three-dimensionally graded ordered mesoporous zeolite, the problem of insufficient catalyst stability and selectivity in the prior art is solved, and efficient and stable catalytic performance and low-cost production are achieved.
Patent Information
- Application Number
- CN202510030051.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The catalysts used in the synthesis of 2-methoxy-4-methylphenol in the prior art have poor stability performance, poor circulation performance, low separation efficiency, low catalytic activity and low product selectivity due to disordered mesoporous structure.
The NiCo@3DZSM-5 catalyst was prepared by using the steam seed-assisted colloidal crystal template (SAC) method to limit the metal domain of the amine coordination in three-dimensional graded orderly mesoporous zeolite, which has the advantages of excellent stability performance, recycling, magnetic separation, and low cost.
The high activity and good selectivity of the catalyst were achieved, and the yield of the product 2-methoxy-4-methylphenol was 100%. The catalyst still maintained high activity and selectivity after 6 cycles, and had good stability and economic value.
Smart Images

Figure CN119771485A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst, belonging to the technical field of catalytic upgrading of lignin model compounds. Background Art
[0002] With the reduction of fossil energy reserves and the increase in the demand for material sources, biomass resources have attracted widespread attention as an alternative renewable clean energy source. Vanillin from lignin is considered to be a potential biomass raw material for the production of 2-methoxy-4-methylphenol (MMP), which has a wide range of applications not only as a high-energy-density fuel but also as an important intermediate for the synthesis of drugs and fragrances. In the past decade, many efficient catalysts for HDO reactions have been designed and synthesized. Due to their high activity, noble metal catalysts such as Pt, Pd and Au-based catalysts have been widely studied. However, the undesirable side reactions caused by poor selectivity and the expensive cost and low reserves of noble metals have greatly limited the large-scale application of noble metals. In recent years, bimetallic catalysts based on alloy nanoparticles (NPs) have been considered to be an effective way to improve the catalytic performance, especially Ni-based catalysts. However, the catalytic performance of bimetallic catalysts is restricted by many factors, such as metal loading, particle dispersion, size, and interaction with the support.
[0003] As a common metal carrier, ZSM-5 zeolite has adjustable acidity, high surface area and excellent thermal / hydrothermal stability, and is widely used in the fields of catalysis and adsorption. However, due to the limited interaction between metal and carrier, the metal substances loaded on the surface are easy to agglomerate during the catalytic reaction, which reduces the utilization rate of metal active sites. Confining the metal active sites inside the zeolite is an effective strategy to solve this problem. However, the narrow microporous structure often constrains the diffusion and mass transfer performance of large-volume reaction substrates, thereby reducing the accessibility of internal metal active sites. Designing hierarchical porous zeolites with both micropores and mesopores is an effective optimization strategy to shorten the diffusion path and solve the diffusion limitation. In existing reports, most of the synthesized hierarchical ZSM-5 zeolites are disordered mesoporous structures, and the pores are difficult to match the reactant size, making it difficult to maximize the utilization of metal sites inside the pores, reducing the catalytic activity. In addition, the disordered structure in the mesoporous pore structure will also limit the diffusion of substrates, leading to a series of side reactions and reducing the selectivity of the product. Therefore, it is urgent to synthesize bimetallic catalysts confined by ordered mesoporous hierarchical zeolites. Summary of the invention
[0004] [Technical issues]
[0005] The problem to be solved by the present invention is that the catalyst used in the prior art for synthesizing 2-methoxy-4-methylphenol has a disordered mesoporous structure and poor stability, resulting in poor circulation performance, low separation efficiency, low catalytic activity and low product selectivity during the synthesis process.
[0006] [Technical solution]
[0007] In order to solve the above problems, the present invention provides a preparation method and application of a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst. The catalyst is prepared by first synthesizing a polystyrene microsphere (PS) template, and then confining an amine-coordinated metal in a three-dimensional hierarchical ordered mesoporous zeolite by a steam seed assisted colloidal crystal template (SAC) method to obtain a NiCo@3DZSM-5 catalyst. The catalyst has the advantages of excellent stability, recyclability, magnetic separation, low cost, etc.
[0008] The first object of the present invention is to provide a method for preparing a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo bimetallic catalyst, which specifically comprises the following steps:
[0009] (1) Styrene is mixed with a NaOH solution and stirred, and then the oil-water phase is separated until the solution no longer appears red, thereby obtaining refined styrene;
[0010] (2) dissolving the refined styrene and polyvinyl pyrrolidone (MW=55000) prepared in step (1) in deionized water, adding styrene and stirring, then deoxygenating the mixture by nitrogen bubbling, adding potassium persulfate aqueous solution to the mixture, and obtaining a polystyrene sphere template by centrifugation;
[0011] (3) tetrapropylammonium hydroxide, anhydrous ethanol, tetraethyl orthosilicate and deionized water are mixed, stirred, and then transferred to an autoclave, and subjected to hydrothermal treatment to obtain a ZSM-5 seed solution;
[0012] (4) mixing aluminum nitrate, tetrapropylammonium hydroxide, anhydrous ethanol and deionized water, and then adding tetraethyl orthosilicate and ZSM-5 seed solution to form a mixed solution;
[0013] (5) adding a nickel precursor coordinated with a complexing agent, a cobalt precursor solution, and a polystyrene sphere template to the mixed solution prepared in step (4), and obtaining a solid powder by vacuum evaporation;
[0014] (6) The solid powder of step (5) is transferred to a stainless steel autoclave, subjected to hydrothermal treatment, cooled, centrifuged, vacuum dried, calcined at high temperature, and then reduced in a H2 atmosphere to obtain a three-dimensional mesoporous zeolite confined NiCo alloy catalyst.
[0015] In one embodiment of the present invention, in step (1), the concentration of the NaOH solution is 0.05-0.15M, more preferably 0.08-0.1M.
[0016] In one embodiment of the present invention, in step (1), the volume ratio of styrene to NaOH solution is 10:2-5, more preferably 10:3.
[0017] In one embodiment of the present invention, in step (2), the addition ratio of refined styrene, polyvinyl pyrrolidone, deionized water and styrene is 10-50 mL: 0.1-0.5 g: 200-700 mL: 10-50 mL, and more preferably 25-30 mL: 0.2-0.3 g: 300-400 mL: 20-30 mL.
[0018] In one embodiment of the present invention, in step (2), the nitrogen bubbling time is 0.5 to 4 hours, more preferably 1 to 1.5 hours, and the temperature is 50 to 100°C.
[0019] In one embodiment of the present invention, in step (3), the molar ratio of tetrapropylammonium hydroxide, anhydrous ethanol, tetraethyl orthosilicate and deionized water is 0.32-0.37:1:0.25:4.5-5.0, and more preferably 0.35:1:0.25:4.8; the stirring time is 12-48 hours, and more preferably 24-28 hours; the hydrothermal treatment temperature is 60-120°C, and more preferably 70-80°C; the hydrothermal time is 48-120 hours, and more preferably 72-78 hours.
[0020] In one embodiment of the present invention, in step (4), the molar ratio of aluminum nitrate, tetrapropylammonium hydroxide, anhydrous ethanol and deionized water is 0.0048:0.15:1:4.8; the addition amount of tetraethyl orthosilicate and ZSM-5 seed solution is 4.5-7.5 g:3-7 mL; the molar ratio of tetraethyl orthosilicate and aluminum nitrate is 45-75:1.
[0021] In one embodiment of the present invention, in step (5), the complexing agent is one of ethylenediamine, ethylenediaminetetraacetic acid, 1,3-propylenediaminetetraacetic acid, and triethylenediamine, preferably ethylenediamine.
[0022] In one embodiment of the present invention, in step (5), the nickel precursor is one of Ni(NO3)2·6H2O, NiCl2·6H2O, Ni(CH3COO)2·4H2O, preferably Ni(NO3)2·6H2O; the cobalt precursor is one of Co(NO3)2·6H2O, CoCl2·6H2O, Co(CH3COO)2·4H2O, preferably Co(NO3)2·6H2O.
[0023] In one embodiment of the present invention, in step (5), the molar ratio of the nickel precursor, the cobalt precursor and the complexing agent is 1:0.5 to 3:20, preferably 1:1 to 1.5:20.
[0024] In one embodiment of the present invention, in step (6), the reactor is equipped with a suspended metal mesh and water at the bottom to avoid direct contact with the precursor and to create a saturated steam environment.
[0025] In one embodiment of the present invention, in step (6), the hydrothermal treatment temperature is 60 to 120° C., more preferably 70 to 80° C.; the hydrothermal time is 48 to 120 h, more preferably 72 to 78 h;
[0026] In one embodiment of the present invention, in step (6), the calcination temperature is 500-800°C, more preferably 550-600°C; the calcination time is 3-8h, more preferably 6-7h; the reduction temperature is 400-700°C, more preferably 500-550°C, and the reduction time is 1-5h, more preferably 2-3h.
[0027] Another object of the present invention is to provide a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst prepared by the above method.
[0028] The present invention also provides the use of the above-mentioned three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst in the hydrogenation and deoxygenation reaction of vanillin.
[0029] In one embodiment of the present invention, the application in the hydrodeoxygenation reaction of vanillin specifically includes: using a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst in the hydrodeoxygenation reaction of vanillin, the amount of vanillin and the catalyst is 1 to 5 mmol: 0.05 to 0.2 g, the reaction temperature is 120 to 220°C, the hydrogen pressure is 0.5-2.5 MPa, the reaction is carried out for 1 to 3 hours, and the solvent is one of deionized water, methanol, ethanol, formic acid, and isopropanol.
[0030] [Beneficial Effects]
[0031] (1) In the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst described in the present invention, the active components Ni and Co species form a synergistic effect, thereby ensuring the activity of the catalyst; in addition, the use of non-precious metals as active components has a high economic value; in addition, by introducing 3DZSM-5 zeolite, the active components are coated and confined, thereby further improving the dispersion of the active components and enhancing the interaction between the metal and the carrier.
[0032] (2) Another advantage of the catalyst described in the present invention is that a protective shell is formed for the active components in a confined manner, thereby suppressing the loss of the active components. The catalyst has a long life and can be used multiple times, which greatly reduces the production cost.
[0033] (3) The process for preparing 2-methoxy-4-methylphenol from vanillin of the present invention is simple, the reaction conditions are mild, the product separation is simple, and it is easy to scale up industrial production.
[0034] (4) The zeolite synthesized by the present invention using polystyrene spheres as templates has uniform pore size and a three-dimensional ordered structure, which is conducive to the contact, diffusion and transfer of reactants inside the pores.
[0035] (5) The present invention synthesizes a three-dimensional hierarchical ordered mesoporous zeolite-confined NiCo alloy catalyst by using polystyrene microspheres as templates, thereby solving the problem of low catalytic activity and low product selectivity caused by the disordered mesoporous structure of the prior art hierarchical ZSM-5 zeolite.
[0036] (6) The catalyst prepared by the present invention is used in the hydrodeoxygenation reaction of vanillin, and the yield of the product 2-methoxy-4-methylphenol is 100%. The catalyst has good recycling performance. After 6 cycles, the yield of the catalyst does not decrease, and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the reaction path diagram;
[0038] Figure 2 It is the GC chromatogram of Example 1;
[0039] Figure 3 The synthetic route diagram of Example 1 is shown in FIG.
[0040] Figure 4 The SEM image (a) of polystyrene and the SEM image (b) of Example 1;
[0041] Figure 5 TEM image of Example 1;
[0042] Figure 6 is the XRD pattern of Example 1;
[0043] Figure 7 It is the N2-physical adsorption isotherm diagram of Example 1 and Comparative Example 1;
[0044] Figure 8 The pore size distribution diagrams of Example 1 and Comparative Example 1; wherein a is the mesopore distribution diagram, and b is the micropore distribution diagram;
[0045] Fig. 9 The cycle performance diagrams of Example 1 and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION
[0046] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0047] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0048] The present invention is further described below in conjunction with specific examples. It should be understood that the following examples are for better explanation of the present invention, rather than for limiting the scope of the present invention. The above catalyst is used for the hydrodeoxygenation reaction of vanillin.
[0049] Sample GC analysis method: NexisGC-2030 was used to analyze the reaction products by gas chromatography; the chromatographic conditions were as follows: the column was a KB-Wax capillary column (30m×0.32mm×0.50μm), the carrier gas was N2; the vaporization chamber temperature was 300℃, the detector temperature was 300℃; the temperature program was: 100℃ for 3min, then heated to 300℃ at a rate of 10℃ / min, and finally kept at 300℃ for 3min. The column flow was adjusted to 1mL / min, the split ratio was 1:50, and the injection volume was 0.2μL.
[0050] Example 1
[0051] This embodiment provides a method for preparing a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst, comprising the following steps:
[0052] (1) 1000 mL of commercially available styrene was mixed with a NaOH solution (0.1 M, 300 mL), stirred vigorously at room temperature, and then the oil-water phase was separated. This was repeated 5 times until the solution no longer showed red, thereby obtaining purified styrene;
[0053] (2) 27 mL of the refined styrene prepared in step (1) and 0.24 g of polyvinyl pyrrolidone (mw=55000) were dissolved in 300 mL of deionized water, 25 mL of commercially available styrene was added and stirred continuously, and then deoxygenated by bubbling nitrogen at 65°C for 1 h. 10 mL of an aqueous solution containing 0.12 g of potassium persulfate was added to the mixture, and after stirring for 24 h, a polystyrene sphere template was obtained by centrifugation.
[0054] (3) 7.2 g of tetrapropylammonium hydroxide, 4.6 g of anhydrous ethanol, 5.2 g of tetraethyl orthosilicate and 8.6 g of deionized water were mixed and stirred at room temperature for 24 h. Then the mixture was transferred to an autoclave and hydrothermally treated at 80 °C for 72 h to obtain a ZSM-5 seed solution.
[0055] (4) 0.18 g of aluminum nitrate, 3.0 g of tetrapropylammonium hydroxide, 4.6 g of anhydrous ethanol and 8.6 g of deionized water were mixed, and then 5.2 g of tetraethyl orthosilicate and 4.5 mL of ZSM-5 seed solution were added to the above solution in sequence and stirred for 3 h to form a mixed solution.
[0056] (5) Add 0.2 mL of ethylenediamine (0.003 mol), 0.045 g of Ni(NO3)2·6H2O and 0.045 g of Co(NO3)2·6H2O solution and 0.3 g of polystyrene balls to the mixed solution prepared in step (4), stir at room temperature for 3 h, and obtain a solid powder by vacuum evaporation;
[0057] (6) The solid powder of step (5) was transferred to a stainless steel autoclave equipped with a suspended metal mesh, hydrothermally treated at 80°C for 72 h, cooled, centrifuged, vacuum dried, calcined at 550°C for 6 h, and then reduced at 550°C in a H2 atmosphere for 3 h to obtain a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst.
[0058] Catalyst structure characterization: Figure 4 a, Polystyrene microspheres are ordered structures with uniform size; Figure 4 b is the catalyst structure, showing long-range order and uniform large pore size; Figure 5 This is the TEM image of Example 1. The synthesized catalyst has no obvious large-sized or aggregated NiCo alloy particles and has high dispersibility. Figure 6 This is the XRD diagram of Example 1. It can be observed that the sample has an MFI structure, and no diffraction peaks corresponding to Ni and Co are detected, indicating that the NiCo particles are successfully and uniformly encapsulated in the ZSM-5 pores. Figure 7 The N2 adsorption-desorption curve of Example 1 shows a type IV isotherm, indicating the presence of a mesoporous structure. Figure 8 This is the pore size distribution diagram of Example 1, confirming that the catalyst has both mesoporous and microporous structures.
[0059] In this example, the catalyst was used in the hydrodeoxygenation reaction of vanillin: 0.12 g of catalyst, 1 mmol of vanillin and 20 mL of deionized water were added to a high-pressure reactor, 2 MPa of H2 was introduced into the reactor, the reaction temperature was 200°C, and the reaction time was 2 h. After the reaction was completed, it was cooled to room temperature, the liquid product was analyzed by gas chromatography, and the conversion rate and selectivity were calculated by quantitative analysis. The results showed that the conversion rate of vanillin was 100%, and the yield of the product 2-methoxy-4-methylphenol was 100%.
[0060] Comparative Example 1
[0061] The only difference from Example 1 is that 3DZSM-5 zeolite is synthesized first, and then Ni(NO3)2·6H2O and Co(NO3)2·6H2O solutions are added, which specifically includes the following steps:
[0062] Synthesis of 3DZSM-5: 1000mL of commercially available styrene was mixed with NaOH solution (0.1M, 300mL), stirred vigorously at room temperature, and then the oil-water phases were separated, and the process was repeated 5 times until the solution no longer showed red color, and refined styrene was obtained. 27mL of refined styrene and 0.24g of polyvinyl pyrrolidone (mw=55000) were dissolved in 300mL of deionized water, 25mL of commercially available styrene was added and stirred continuously, and then deoxygenated with nitrogen bubbling at 65°C for 1h, 10mL of an aqueous solution containing 0.12g of potassium persulfate was added to the mixture, and after stirring for 24h, a polystyrene sphere template was obtained by centrifugation. 7.2g of tetrapropylammonium hydroxide, 4.6g of anhydrous ethanol, 5.2g of ethyl orthosilicate and 8.6g of deionized water were mixed and stirred at room temperature for 24h. Then it was transferred to an autoclave and hydrothermally treated at 80°C for 72h to obtain a ZSM-5 seed solution. 0.18g aluminum nitrate, 3.0g tetrapropylammonium hydroxide, 4.6g anhydrous ethanol and 8.6g deionized water were mixed, and then 5.2g tetraethyl orthosilicate and 4.5mL ZSM-5 seed solution were added to the above solution in sequence and stirred for 3h to form a mixed solution. 0.2mL ethylenediamine and 0.3g polystyrene balls were added to the mixed solution, stirred at room temperature for 3h, and solid powder was obtained by vacuum evaporation; then it was transferred to a stainless steel autoclave, hydrothermally treated at 80℃ for 72h, cooled, centrifuged, vacuum dried, calcined at 550℃ for 6h, and then reduced at 550℃ in H2 atmosphere for 3h to obtain 3DZSM-5 zeolite.
[0063] The NiCo / 3DZSM-5 catalyst was prepared as follows: 0.3 g 3DZSM-5, 0.2 mL ethylenediamine, 0.045 g Ni(NO3)2·6H2O and 0.045 g Co(NO3)2·6H2O, and 50 mL deionized water were mixed, stirred at room temperature for 12 h, vacuum dried, calcined at 550 °C for 6 h, and then reduced at 550 °C in a H2 atmosphere for 3 h to obtain the NiCo / 3DZSM-5 catalyst.
[0064] The results showed that the conversion rate of vanillin was 93.67% and the yield of 2-methoxy-4-methylphenol was 72.58%.
[0065] Comparative Example 2
[0066] The only difference from Example 1 is that conventional microporous ZSM-5 zeolite (CZSM-5) is synthesized first, and then Ni(NO3)2·6H2O and Co(NO3)2·6H2O solutions are added. The conditions for the hydrodeoxygenation of vanillin are the same as those in Example 1.
[0067] Synthesis of conventional microporous ZSM-5 zeolite (CZSM-5): The molar ratio of the initial reaction mixture was 100SiO2:1Al2O3:5Na2O:25TPAOH:4000H2O. Initially, 0.19 g NaOH was stirred with 9.49 g TPAOH and 33.61 g deionized water at room temperature for 30 min. Subsequently, 0.35 g Al(NO3)3·9H2O was added to the mixture and stirring was continued at 60°C for 1 h. Then 9.72 g TEOS was added to the mixture and then stirred at 60°C for 1 h. The resulting precursor was then transferred to an autoclave and heated in an oven at 180°C for 48 h. After centrifugation, the solid product was collected and then calcined at 550°C for 6 h.
[0068] The NiCo / CZSM-5 catalyst was prepared as follows: 0.3 g CZSM-5, 0.2 mL ethylenediamine, 0.045 g Ni(NO3)2·6H2O and 0.045 g Co(NO3)2·6H2O, and 50 mL deionized water were mixed, stirred at room temperature for 12 h, vacuum dried, calcined at 550 °C for 6 h, and then reduced at 550 °C in a H2 atmosphere for 3 h to obtain the NiCo / CZSM-5 catalyst.
[0069] The results showed that the conversion rate of vanillin was 43.72%, and the yield of 2-methoxy-4-methylphenol was 43.72%.
[0070] Example 2
[0071] The only difference from Example 1 is that ethylenediaminetetraacetic acid is used to replace ethylenediamine, and other parameters and conditions are the same as those in Example 1.
[0072] The results showed that the conversion rate of vanillin was 99.98% and the yield of 2-methoxy-4-methylphenol was 80.11%.
[0073] Example 3
[0074] The only difference from Example 1 is that 1,3-propylenediaminetetraacetic acid is used to replace ethylenediamine, and other parameters and conditions are the same as those in Example 1.
[0075] The results showed that the conversion rate of vanillin was 99.69% and the yield of 2-methoxy-4-methylphenol was 85.65%.
[0076] Example 4
[0077] The only difference from Example 1 is that triethylenediamine is used to replace ethylenediamine, and other parameters and conditions are the same as those in Example 1.
[0078] The results showed that the conversion rate of vanillin was 51.48%, and the yield of 2-methoxy-4-methylphenol was 51.48%.
[0079] Example 5
[0080] The only difference from Example 1 is that CoCl2·6H2O is used to replace Co(NO3)2·6H2O, and the other parameters and conditions are the same as those in Example 1.
[0081] The results showed that the conversion rate of vanillin was 100%, and the yield of 2-methoxy-4-methylphenol was 86.17%.
[0082] Example 6
[0083] The only difference from Example 1 is that Co(CH3COO)2·4H2O is used to replace Co(NO3)2·6H2O, and the other parameters and conditions are the same as those in Example 1.
[0084] The results showed that the conversion rate of vanillin was 100%, and the yield of 2-methoxy-4-methylphenol was 94.26%.
[0085] Comparative Example 3
[0086] The only difference from Example 1 is that no polystyrene sphere template is added, and other parameters and conditions are the same as those in Example 1.
[0087] The results showed that the conversion rate of vanillin was 86.79% and the yield of 2-methoxy-4-methylphenol was 42.65%.
[0088] Comparative Example 4
[0089] The difference from Example 1 is that Co(NO3)2·6H2O is replaced by Cu(NO3)2·6H2O, and the other parameters and conditions are the same as those in Example 1.
[0090] The results showed that the conversion rate of vanillin was 100%, and the yield of 2-methoxy-4-methylphenol was 80.92%.
[0091] Comparative Example 5
[0092] The difference from Example 1 is that Co(NO3)2·6H2O is replaced by Zn(NO3)2·6H2O, and the other parameters and conditions are the same as those in Example 1.
[0093] The results showed that the conversion rate of vanillin was 67.44%, and the yield of 2-methoxy-4-methylphenol was 67.23%.
[0094] Comparative Example 6
[0095] The difference from Example 1 is that Co(NO3)2·6H2O is replaced by Fe(NO3)2·6H2O, and the other parameters and conditions are the same as those in Example 1.
[0096] The results showed that the conversion rate of vanillin was 71.07% and the yield of 2-methoxy-4-methylphenol was 70.52%.
[0097] Stability test analysis
[0098] The catalysts in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to a cycle test. The specific results are as follows: Fig. 9 It can be seen that the confined catalyst has good cycle performance. After 6 cycles, the activity and selectivity of the catalyst have not decreased significantly. The conversion rate of vanillin and the yield of 2-methoxy-4-methylphenol can still reach more than 95% and 90%, respectively, showing good stability.
[0099] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst, characterized in that: The steps include: (1) Mixing styrene with a NaOH solution, separating the oil-water phase, and repeating until the solution no longer appears red, thereby obtaining refined styrene; (2) dissolving purified styrene and polyvinyl pyrrolidone in deionized water, adding styrene and continuously stirring, then deoxygenating with nitrogen bubbling, and finally adding potassium persulfate aqueous solution and centrifuging to obtain a polystyrene sphere template; (3) tetrapropylammonium hydroxide, anhydrous ethanol, tetraethyl orthosilicate and deionized water are mixed, transferred to an autoclave, and subjected to hydrothermal treatment to obtain a ZSM-5 seed solution; (4) mixing aluminum nitrate, tetrapropylammonium hydroxide, anhydrous ethanol and deionized water, and then adding tetraethyl orthosilicate and ZSM-5 seed solution to form a mixed solution; (5) adding a nickel precursor and a cobalt precursor solution coordinated with a complexing agent and polystyrene balls to the mixed solution prepared in step (4), and obtaining a solid powder by vacuum evaporation; (6) The solid powder of step (5) is transferred to an autoclave, subjected to hydrothermal treatment, cooled, centrifuged, vacuum dried, calcined, and then reduced in a H2 atmosphere to obtain a three-dimensional mesoporous zeolite confined NiCo alloy catalyst.
2. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (1), the concentration of the NaOH solution is 0.05-0.15 M; the volume ratio of styrene to the NaOH solution is 10:2-5.
3. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (2), the amount of refined styrene, polyvinyl pyrrolidone and deionized water is 10-50 mL: 0.1-0.5 g: 200-700 mL; the amount of polyvinyl pyrrolidone and styrene is 0.1-0.5 g: 10-50 mL.
4. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (3), the molar ratio of tetrapropylammonium hydroxide, anhydrous ethanol and tetraethyl orthosilicate is 0.32-0.37:1:0.25, and the molar ratio of tetraethyl orthosilicate and deionized water is 0.25:4.5-5.0; the hydrothermal treatment temperature is 60-120° C., and the hydrothermal time is 48-120 h.
5. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (4), the molar ratio of aluminum nitrate, tetrapropylammonium hydroxide, anhydrous ethanol and deionized water is 0.0048:0.15:1:4.8; the added amount of tetraethyl orthosilicate and ZSM-5 seed solution is 4.5-7.5 g:3-7 mL; and the molar ratio of tetraethyl orthosilicate and aluminum nitrate is 45-75:
1.
6. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (5), the complexing agent is one of ethylenediamine, ethylenediaminetetraacetic acid, 1,3-propylenediaminetetraacetic acid, and triethylenediamine; the nickel precursor is one of Ni(NO3)2·6H2O, NiCl2·6H2O, and Ni(CH3COO)2·4H2O; and the cobalt precursor is one of Co(NO3)2·6H2O, CoCl2·6H2O, and Co(CH3COO)2·4H2O.
7. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (5), the molar ratio of the nickel precursor, the cobalt precursor and the complexing agent is 1:0.5 to 3:
20.
8. The method for preparing the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 1, characterized in that: In step (6), the hydrothermal treatment temperature is 60-120° C., and the hydrothermal time is 48-120 h; the roasting temperature is 500-800° C., and the roasting time is 3-8 h; the reduction temperature is 400-700° C., and the reduction time is 1-5 h.
9. A three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst prepared by the method of any one of claims 1 to 8.
10. Use of the three-dimensional hierarchical ordered mesoporous zeolite confined NiCo alloy catalyst according to claim 9 in the hydrodeoxygenation reaction of vanillin.
Citation Information
Patent Citations
Method for effectively separating raceme and preparing homochiral substance
CN102392066A
Preparation method and application of hierarchical porous MFI nanosheets with surface modified with highly-dispersed Ni (Ni-MFI-NSs)
CN106076402A
Method for preparing arene from methyl alcohol based on catalytic effect of zeolite molecular sieve with porous structure
CN106986735A
Hierarchical pore ZSM-5 molecular sieve packaged Ni metal catalyst with micropores and mesopores as well as preparation method and application of hierarchical pore ZSM-5 molecular sieve packaged Ni metal catalyst
CN115007197A
Dead time controller and DC-CD converter including the same
KR1020220124417A
Cited By
Powder-loaded nickel catalyst and preparation method and application thereof
CN122298436A